Morphological features of a patient with progeroid phenotype - М. А. Korzhenevskaya; S. V. Kashina; Т. L. Gindina; О. L. Romanova; V. А. Seredina; S. А. Laptiev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2024)
Currently, in medical genetics, there is a significant gap between real medical care and scientific achievements in the field of molecular biological technologies. The diagnosis of hereditary pathology is made infrequently, and genetic knowledge is slowly entering medical practice. Most patients with hereditary disorders are under completely different diagnoses and are treated by specialists according to the principle of the leading clinical symptom, such as, for example, mental retardation, skeletal deformities, ocular pathology, hearing loss, atrophic, ichthyosis-like or psoriasiform skin changes, etc. The clinic of hereditary diseases is often similar to well-known and frequently occurring diseases, since there is a phenotypic similarity of genetically heterogeneous diseases. Misdiagnosis leads to pathogenetically unjustified treatment. In our work, we described a clinical case of progeroid syndrome that confirmed by cytogenetic diagnostics based on the Pavlov University (Saint Petersburg, Russia). The patient has been observed with various dermatological syndromes for 26 years. With a multidisciplinary approach to the verification of hereditary disease, dermatovenerologists and geneticists were able to define the hereditary nature of the skin lesion in the patient and confirm her progeroid syndrome.